2015
DOI: 10.2220/biomedres.36.247
|View full text |Cite
|
Sign up to set email alerts
|

<b>Structure of the methyl orange-binding site on human serum albumin and its color-change </b><b>mechanism </b>

Abstract: The goal in this study was to clarify the color-change mechanisms of methyl orange (MO) bound to human serum albumin (HSA) and the structure of the binding site. The absorbance of the MO-HSA complex was measured at 560 nm in solutions of varying pH (pH 2.4-6.6). The obtained pHdependent experimental data were consistent with the data calculated using the HendersonHasselbalch equation and pKa values (3.8, MO; 1.4, carboxyl group). The extent of the binding of MO to an HSA molecule was determined to be 1-4 by pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…6). Very recently, Ito and Yamamoto have investigated absorbance of the MO-human serum albumin (HSA) complex at 560 nm in the solutions with various pH values (pH 2.4-6.6) (25). Also, they have used surface plasmon resonance (SPR) analysis for confirming MO-HSA binding and reported that one or two MO molecules bind to a HSA molecule at pH 3.6-7.2 (25).…”
Section: Bsa Dying With Momentioning
confidence: 99%
See 1 more Smart Citation
“…6). Very recently, Ito and Yamamoto have investigated absorbance of the MO-human serum albumin (HSA) complex at 560 nm in the solutions with various pH values (pH 2.4-6.6) (25). Also, they have used surface plasmon resonance (SPR) analysis for confirming MO-HSA binding and reported that one or two MO molecules bind to a HSA molecule at pH 3.6-7.2 (25).…”
Section: Bsa Dying With Momentioning
confidence: 99%
“…In this method, the protein and dye molecules, MO, form a complex. Color change of the MO-protein complex is caused by a proton-exchange reaction, and its intensity depends on the pH of the reaction solution (25). Easy handling is another advantage of this method.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is likely that a basic residue deprotonates the phenolic -OH, and hence a large red shift (~ 35 nm) of absorption maxima was observed when HSA was added into the solution of 2 at physiological buffer (figure 4). 49…”
Section: Resultsmentioning
confidence: 99%
“…It may also interact with hydrophobic patches on proteins or other macromolecules containing such patches. For example, interactions with human serum albumin have been reported (Ito & Yamamoto, 2015). To our knowledge, methyl orange alone does not interact with DNA; however, when used in Lenoir et al…”
Section: Troubleshootingmentioning
confidence: 94%